PERAN WORLD WILDLIFE FUND (WWF) DALAM MENGIMPLEMENTASIKAN WORLD CONSERVATION STRATEGY (WS) DIPROVINSI RIAU PADA TAHUN 2010-2015 - Siallagan, Desbin Raja Irsanto; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research aims to explain the role of World Wide Fund for Nature (WWF) on implementing World Conservation Strategy (WCS) in Riau in 2010-2015. WCS is a world strategy for making a sustainable-development condition,by doing both development and conservation. WCS also a cooperation program beetwen IUCN, UNEP, WWF, Fao and Unesco.Method used in this research is qualitative research. This research uses secondary data obtained from books, journal, internet, news and other media. The author apply group behavior as the research level analysis which is World Wide Fund for Nature (WWF).This research analyzed its data by using Pluralism perspective and Green Politisc Theory by Eckersley. Also, writer did an interview to konservator in WWF and do an observation on field.The result of this research shows that WWF already carried out its role as practitioner of WCS by doing conservation in various places in Riau. Though WWF is not center in development program, WWF also helps rural people to make a living while still concern environmental stability.Keyword: WCS, conservation, conservator, practitioner, sustainable-development,cooperation.